Проблемы изучения севернорусского слова дак: достижения и недостаткищ (Advantages and Shortcomings of Different Perspectives in Describing Northern Russian dak) - Post, Margje (Poljarnyj vestnik, 2002)
The word dak is one of several highly frequent particles, used in most Northern Russian and some Siberian dialects. It can occur sentence ini- tially, sentence internally and sentence finally to connect two parts of the discourse, such as words, sentences, and presuppositions. This article describes the advantages and shortcomings of six dif- ferent perspectives which have been used to describe this unspecified, multifunctional word: descriptions in traditional grammatical terms, in syntactic terminology used for spontaneus speech, research on its role in information structure, its use in discourse, the role of prosody, and finally comparisons with parallel words in neighbouring and other languages. I conclude that a combination of approaches is required for a better understanding of the way dak functions. Studies in prosody combined with research on dak's role in information structure appear to be most fruitful, and modern theories of discourse structure, which are almost completely ignored at present, could be helpful. Much research remains to be done, especially to clarify the restrictions on the use of the word dak and the way it functions in less obvious contexts.